SIRT4 and SIRT6 Serve as Novel Prognostic Biomarkers With Competitive Functions in Serous Ovarian Cancer - Huihuan Wang (Frontiers in Genetics, 2021)
Sirtuins (SIRTs) are class III histone deacetylases (HDACs) that include seven members and are widely expressed in mammals. Accumulating evidence shows that sirtuins may have contradictory roles in various malignancies. They mainly participate in metabolic homeostasis, DNA damage repair, cell survival, and differentiation, as well as other cancer-related biological processes. To better understand their prognostic role and biological functions, we used comprehensive bioinformatic analyses to demonstrate the expression and mutation of sirtuin family member genes in ovarian cancer (OC), with a detailed focus on prognostic prediction, including the effectiveness of anti-OC drugs. Furthermore, the co-expression genes of SIRT4 and SIRT6 with contradictory survival prediction values in both overall and progression-free survival (PFS) times were further analyzed through Gene Ontology enrichment and Kyoto Encyclopedia annotation. Additionally, we performed and obtained the immunohistochemical staining patterns of these two biomarkers from the serous OC patient database and clinical patient samples to demonstrate their potential applicability in clinical pathology. According to our findings, SIRT4 and SIRT6 are novel prognostic biomarkers that may serve as contradictory competitors for OC cell survival. They are also sensitive biomarkers for the prediction of Avastin’s anticancer effect. While SIRT4 is related to the immune response during oocyte maturation, SIRT6 participates in immune-related disease pathways and mitochondrial metabolism-mediated DNA translation. These findings contribute to the novel hypothesis that SIRT4 and SIRT6 act as contradictory competitors in the regulation of OC behavior. Further studies are required to validate our hypothesis.